Comprehensive planet gear diagnostics: Use of transmission error and mesh phasing to distinguish localised fault types and identify faulty gears. (15th July 2019) - Peng, Dikang; Smith, Wade A.; Borghesani, Pietro; Randall, Robert B.; Peng, Zhongxiao
Highlights: Tooth spalls and cracks change transmission error in different ways. Vibration features of spalls and cracks are simulated and measured. Timing of fault-related events can be used to distinguish different fault types. Mesh phasing can be used to identify which planet is faulty. A comprehensive diagnostic procedure for planet gears is presented. Abstract: Planetary gearboxes have a wide range of applications, but due to their complex layout, the diagnostics of planetary gearboxes is more challenging than that of fixed-axis gearboxes. This is especially so for planet gears, as multiple planets mesh simultaneously, share the same rotating speed and are in mesh with both the sun and ring gears. To enable the development of reliable diagnostic and, even more critically, prognostic algorithms, the detection of a fault needs to be complemented with information about its location and the dominant failure mode. In this study, we present a comprehensive procedure to diagnose localised planet gear faults, adding to fault detection the differential diagnosis of cracks and spalls and the identification of the faulty planet. To do this, first the transmission error (TE) of planet cracks and spalls is investigated using a finite element model. This is aimed at providing a thorough understanding of how these two types of faults result in different excitations of the system. A lumped parameter model (LPM) is then used to link the changes in TE to specific vibration patterns, which are identified as characteristic of either tooth cracks or spalls. These observations are then combined with a recently proposed concept that uses mesh phasing to identify which planet gear carries a fault, resulting in a comprehensive framework that can both diagnose the type of fault and determine which planet gear it is on. The methodology is verified using experimental data obtained from a planetary gearbox test rig.